도덕심리학에서 상보성 논제의 도덕교육적 의의와 한계 - 이정렬; Jeong Ryeol Lee (윤리연구, 1(73), 2009)
자연주의적 오류를 피하기 위해 도덕철학적 전제를 바탕으로 도덕심리학 연구를 해야 한다는 콜버그의 문제 의식은 동형론을 거쳐 상보성 논제로 정립되었다. 하지만 최근 도덕심리학에서 상보성 논제는 ‘경계 문제’와 ‘현상주의 원칙에 대한 논쟁’이라는 쟁점을 통해 새로운 비판에 직면하고 있다. 본 논문은 상보성 논제의 쟁점을 통해 상보성의 진정한 의미를 재조명하고 상보성 논제가 도덕교육이라는 큰 틀 안에서 심리학과 도덕철학의 관계와 역할 정립에 대한 논의로 이어져야 한다는 것을 주장하였다. 도덕교육의 영역에서 상보성은 두 학문간의 경계와 한계를 인식하는 적극적인 구분선을 의식할 때 오히려 그 의미가 더욱 구현될 수 있다. 이러한 구분선은 두 학문의 배타성을 강조하는 것이라기보다는 도덕교육이라는 위대한 실행을 위한 소통의 전제라고 할 수 있다. 또한 본 논문은 도덕철학의 형이상학적 특성과 심리학의 과학적 특성으로 인해 도덕성에 대한 완전한 합의에 이르지 못하며 이것은 상보성 논제의 한계로 남을 수밖에 없음을 강조하였다. 하지만 이러한 한계를 내재한 상보성 논제는, 분명한 답을 제공해주기보다는 오히려 중요한 질문들이 무엇인지 드러나게 해줌으로써 도덕교육에 대한 진지한 논의로 이끌 수 있음을 주장하였다. Kohlberg's critical awareness, that a study on moral psychology should be made on the grounds of a moral philosophical presumption in order to avoid naturalistic fallacy was established as a complementarity thesis through isomorphism. However, complementarity thesis in the latest moral psychology is facing a new criticism through a point at issue, namely, a 'boundary problem' and a 'dispute about the principle of phenomenalism'. This paper insisted that it is necessary to illuminate the true meaning of complementarity again through the point at issue of complementarity and that the thesis should lead to a discussion about the establishment of the relationship between and the roles of psychology and moral philosophy within the larger framework of moral education. In the area of moral education, the meaning of complementarity may be more realizable when becoming aware of the active contour that perceives the border between and the limitations of the two sciences. Such a contour would be a presumption of communications for the great execution of moral education rather than an emphasis on the exclusiveness of the two sciences. Also, this paper accentuated the fact that it is unable to reach a perfect agreement on morality due to the metaphysical characteristics of moral philosophy and the scientific characteristics of psychology, and these cannot help remaining as the limitations of the complementarity thesis. But still, the paper asserted that the complementarity thesis, in which these limitations are imminent, is able to lead us to a serious discussion about moral education by revealing crucial questions rather than providing clear answers. KCI Citation Count: 4